Measuring on Sugar Content of Sugarcane Based on Phase Locked Loop with Capacitive Sensor - Siriporn Nonta; Anucha keawphusuk; Paramote Wardkein (My University, 2018)
The article proposes instrument construction for measuring the sugar content in sugarcanes juice. A interdigital capacitor acting as a sensing element is connected with the sinusoidal generator. Whose output frequency depends on changing the capacitance of interdigital capacitor. To convert the frequency to the direct current (DC) voltage. A sin wave from the generator is converted square wave by comparator circuit before feeding to the phase locked loop circuit. Finally, the DC voltage is changed to concentration of the sugar content in sugarcanes juice
Keywords: Square wave; Content (measure theory); Spectroscopy and Chemometric Analyses